Structure Characterization And Nonlinear Optical Properties Of Novel Chalcone Derivatives: Experimental And Computational Investigations - Ramzi, Farah Diana (2024)
Eight fluoro methoxyphenyl chalcones derivatives (1-8) with varying substitution groups were synthesized by the claisen-schmidt condensation method and crystallized using slow evaporation techniques. The compounds were characterized using ftir and nmr, as well as the 3d structural determination by scxrd. Hirshfeld surface analysis revealed that crystal packing and molecular conformation were stabilized through hydrogen bonding, π–π stacking, and halogen interactions. The molecular properties were determined using mep and npa analyses. The linear and 3rd-order nonlinear optical properties were studied theoretically (using dft and tddft) and experimentally (using uv-vis spectrometer and z-scan technique). The theoretical studies indicate that the absorption peak of compounds 1–8 is mainly contributed by an electronic transition from the ground state to the second excited state (s0→s2), with an excitation energy ranging from 4.17 to 4.29 ev, and transition electric dipole moment of 2.763 to 2.885 a.U. The experimental studies determined the two-photon absorption (2pa) of all compounds is mainly attributed to their nonlinear absorption (nla) in the non-resonant laser regime, consistent with the trend of dynamic